The roles of self-compassion and psychological flexibility in the psychological well-being of adolescent girls - Mendes, Ana Laura (2022)
Research has suggested that the perception of life satisfaction and quality of life tends to decrease during adolescence, and points out that adolescent girls tend to report lower levels of psychological well-being when compared with adolescent boys. Furthermore, studies have highlighted the role of affiliation indicators in the psychological well-being of adolescent girls. However, the study of the mechanisms that mediate this relationship remains scarce. Thus, the current study intends to explore the roles of self-compassion attitudes and psychological flexibility in association between early affiliative memories and current feelings of social safeness and the psychological well-being of girls, through path analysis. The study was conducted with 221 female adolescents, between 12 and 18 years of age, who completed self-report measures. The path model accounted for 22%, 17%, 18% and 52% of the variances of current feelings of social safeness, self-compassion attitudes, psychological flexibility and psychological well-being of adolescent girls, respectively, and revealed a very good fit. Results showed that early affiliative memories and the experience of feeling safe in current social relationships were positively related to psychological well-being of girls through higher levels of self-compassion and psychological flexibility. These findings suggest that not only affiliation indicators are important for the psychological well-being of adolescent girls but also the presence of specific adaptive emotion regulation processes. Prospective studies should further confirm these findings. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.